Distinguishing Erosive Lichen Planus From Differentiated Vulvar Intraepithelial Neoplasia. Issue 2 (April 2016) - Day, Tania; Bowden, Nikola; Jaaback, Ken; Otton, Geoff; Scurry, James
Abstract : Objective: Erosive lichen planus (LP) and differentiated vulvar intraepithelial neoplasia (dVIN) may display overlapping histopathologic features. Materials and Methods: We searched the local pathology database for vulvar biopsies reported as dVIN or erosive vulvitis during 2011 to 2013 inclusive. After review of patient notes and slides, there were 5 cases with a clinical appearance and course consistent with erosive LP and histopathology showing epithelial regeneration. We then selected 5 cases of dVIN in which the clinical course and histopathology supported the diagnosis. We performed immunohistochemistry for p16 and p53 on all cases and did copy variant analysis on 1 case each of erosive LP and dVIN. Results: Histopathology of the LP cases showed epithelial thinning, absent stratum corneum, lack of maturation, as well as nuclear changes of enlargement, pleomorphism, and hyperchromasia. Three LP cases (60%) showed a wild-type p53 pattern and 2 (40%) were confluent positive. Two dVIN cases (40%) showed full-thickness loss of differentiation. One case (20%) of dVIN was p53 negative, 2 (40%) were wild-type, 1 was confluent positive, and 1 showed dark suprabasilar staining. All cases were negative for p16. Compared with control, erosive LP epithelium showed a similar copy-number pattern, whereas the dVIN epithelium had many copy-number changes. Conclusions: A small subset of clinically diagnosed vulvovaginal erosive LP will show on histopathology a regenerative erosive vulvitis with loss of epithelial maturation and nuclear changes, which requires clinicopathologic correlation to distinguish from dVIN. Abstract : Erosive lichen planus and differentiated vulvar intraepithelial neoplasia may closely resemble each other histologically and require clinicopathological correlation to be distinguished.